1996
DOI: 10.1111/j.1440-1746.1996.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and factors influencing portal hypertensive gastropathy and duodenopathy in cirrhotic portal hypertension

Abstract: Portal hypertensive gastropathy and duodenopathy are distinct clinical and endoscopic entities. Data on factors influencing the development of these lesions are still emerging. Data on portal hypertensive duodenopathy are scarce. We prospectively studied 230 patients with liver cirrhosis and oesophageal varices attending the liver clinic of the Sanjay Gandhi Post Graduate Institute of Medical Sciences. One hundred and forty-two patients had no history of upper gastrointestinal bleeding, while the remainder had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 21 publications
3
44
2
Order By: Relevance
“…The finding of small-bowel manifestations of PTH in non-cirrhotic patients is in accordance with reports in the literature about PHG and PHC. Indeed, although the prevalence is a matter of debate, with a large series from India reporting a figure as high as 62% [28], the presence of PHG is well documented in non-cirrhotic patients with PTH [29]. The absence of a linear relationship between the severity of liver disease and the prevalence of the PHG, as stated by Primignani et al [2], reinforces the conviction that the presence of cirrhosis is not a sine qua non condition for the occurrence of PHG.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of small-bowel manifestations of PTH in non-cirrhotic patients is in accordance with reports in the literature about PHG and PHC. Indeed, although the prevalence is a matter of debate, with a large series from India reporting a figure as high as 62% [28], the presence of PHG is well documented in non-cirrhotic patients with PTH [29]. The absence of a linear relationship between the severity of liver disease and the prevalence of the PHG, as stated by Primignani et al [2], reinforces the conviction that the presence of cirrhosis is not a sine qua non condition for the occurrence of PHG.…”
Section: Discussionmentioning
confidence: 99%
“…Primignani et al [34] confirmed the correlation of PHG with severity of portal hypertension, by correlating PHG with presence and size of esophageal varices. Sacchetti et al [24] Cirrhosis 142 38 (27%) 28 (20%) 10 (7%) D'Amico et al [25] Cirrhosis 212 130 (61%) 110 (52%) 20 (9%) Calès et al [26] Cirrhosis 100 98 (98%) 57 (57%) 41 (41%) Rabinovitz et al [27] Cirrhosis 510 (43%) Not reported Not reported Iwao et al [28] Cirrhosis 47 32 (68%) 15 (32%) 17 (36%) Taranto et al [29] Cirrhosis 394 317 (80.5%) Not reported Not reported Gupta et al [30] Cirrhosis 230 (61%) (52%) (9%) Iwao et al [31] Cirrhosis 476 254 (53%) 208 (43%) 46 (9%) Carpinelli et al [32] Cirrhosis 566 362 (64%) 192 (34%) 170 (30%) Zaman et al [33] Cirrhosis 120 74 (62%) 47 (39%) 27 (23%) Primignani et al [34] Cirrhosis 373 299 (80%) 127 (34%) 172 (46%) Chaves et al [35] Cirrhosis vs schistosomiasis 43 18 (81%) vs 7 (33%) Not reported Not reported Merkel et al [36] Cirrhosis 62 49 (79%) 29 (46%) 20 (32%) Merli et al [37] Cirrhosis, with mild portal hypertension 222 48 (21%) 43 (19%) 5 (2%) Ito et al [38] Cirrhosis 47 13 (27%) 10 (21%) 3 (6%) De Palma et al [39] Cirrhosis 37 23 (62%) Not reported Not reported Menchén et al [40] Cirrhosis 549 353 (64%) 275 (50%) 77 (14%) Yüksel et al [41] Cirrhosis 114 total 76 (66%) 38 (33%) 38 (33%) Fontana et al [42] Cirrhosis or bridging fibrosis from hepatitis C 1016 374 (37%) 345 (34%) 29 (3%) Bresci et al [43] Cirrhosis 85 36 (42%) Not reported Not reported Akatsu et al [44] End stage liver disease 29 19 (65.5%) 18 (62.1%) 1 (3.4%) Zardi et al [45] Cirrhosis 266 84 (31%) Not reported Not reported Barakat et al [46] Cirrhosis with portal hypertensive duodenopathy 105 105 (100%) 17 (16.2%) 88 (83.8%) Bellis et al [47] Cirrhosis 59 44 (76%) 16 (27%) 28 (47%) Gravante et al [48] Liver transplant candidates with cirrhosis 80 41 (51.2%) Not reported Not reported Canlas et al [49] [58] Cirrhosis 611 448 (73.3%) 37.3% 36% Abbasi et al [59] Cirrhosis 102 87 (85%) Not reported Not reported Ahmed et al …”
Section: (50%) Not Reported Not Reportedmentioning
confidence: 99%
“…Contrariwise, a decided minority of studies showed no significant association between severity of portal hypertension and rate of PHG [8,9,16,26,28,30,31,47,54,67] .…”
Section: (50%) Not Reported Not Reportedmentioning
confidence: 99%
“…The prevalence of PHG was higher in those patients with oesophagogastric varices (69%) compared with patients with oesophageal varices alone (55%). 11 Primignani et al 12 suggested a correlation exists between PHG and the severity of portal hypertension, as the prevalence of gastropathy was higher in patients with large EV than in those with small varices. However in a study done by Bellis et al 13 this association is weak as also reflected by the results of my study.…”
Section: Discussionmentioning
confidence: 99%